2002
DOI: 10.1046/j.1523-1747.2002.19623.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immunosuppressive 1α,25-Dihydroxyvitamin D3 Analog with Reduced Hypercalcemic Activity

Abstract: 1Alpha,25-dihydroxyvitamin D3, the biologically active form of vitamin D3, is a potent immunomodulatory molecule; however, its clinical use as an immunosuppressant is limited due to its strong effects on calcium homeostasis and the risk of associated side-effects. Here, we present a representative of a novel class of vitamin D analogs that exhibits potent immunosuppressive activity in a murine model of contact hypersensitivity when applied systemically and is efficacious also at nonhypercalcemic dosages. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
1
47
0
3
Order By: Relevance
“…9; P < 0.05). As demonstrated previously [26] , the calcitriol compound did not increase serum levels of calcium in a significant manner, as compared to serum calcium levels in control animals (data not shown).…”
Section: Treatment With Zk191784 Ameliorates Acute and Chronic Dss-insupporting
confidence: 84%
See 3 more Smart Citations
“…9; P < 0.05). As demonstrated previously [26] , the calcitriol compound did not increase serum levels of calcium in a significant manner, as compared to serum calcium levels in control animals (data not shown).…”
Section: Treatment With Zk191784 Ameliorates Acute and Chronic Dss-insupporting
confidence: 84%
“…However, calcitriol has clear dose-limiting hypercalcemic effects that interfere with its systemic clinical use due to strong influence on calcium homeostasis and the risk of associated side effects. Recently, ZK191784, a new low-calcemic calcitriol derivative, has been identified that inhibits lymphocyte proliferation and suppresses secretion of proinflammatory cytokines by monocytes [26] . The compound has shown immunosuppressive activity in a murine contact hypersensitivity model when given systemically at concentrations that do not cause hypercalcemic effects, thereby suggesting a possible therapeutic application as an immunosuppressive agent [26] .…”
Section: Cd25mentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Besides other properties, calcitriol has profound effects on immunoregulation and its analog ZK 191784 has an immunosuppressive impact. 19,20 The aim of the present study was to investigate the contribution of OPN to remodeling processes in enterovirusinduced myocarditis and subsequent DCM. We used the murine model of CVB3-induced myocarditis, in which susceptible A.BY/SnJ mice develop chronic myocarditis and severe cardiac fibrosis following acute infection resulting from a restricted type of virus persistence, whereas resistant C57BL/6 mice eliminate the virus during acute infection without evolving significant fibrosis.…”
mentioning
confidence: 99%